Synthesized speech output and children: a scoping review. - Drager KDR; Reichle J; Pinkoski C (American Journal of Speech-Language Pathology, 2010)
Purpose: Many computer-based augmentative and alternative communication systems in use by children have speech output. This article (a) provides a scoping review of the literature addressing the intelligibility and listener comprehension of synthesized speech output with children and (b) discusses future research directions. Method: Studies investigating synthesized speech intelligibility and/or comprehension with children as listeners were systematically identified and coded according to their objectives and methodology. Results: Ten studies were identified. They were organized according to the following variables: intelligibility variables related to the stimuli (context and rate), intelligibility variables related to aspects of the listener (age of the child, the language or languages spoken by the listener, experience, and practice effects), and comprehension. Each of these factors--and the research support with child participants--was discussed. Conclusions: Overall, there is a paucity of research investigating synthesized speech for use with children. Available evidence suggests that children produce similar trends but lower levels of intelligibility performance when compared with adults. Future areas of applied research are required to adequately define this relationship and the variables that may contribute to improving the intelligibility and comprehension of synthesized speech for children.